Effect of operation mode on membrane fouling from traditional Chinese medicine water extracts. (August 2022) - Liu, Hongbo; Tao, Xingbao; Zhu, Huaxu; Tang, Zhishu; Xu, Sining; Li, Bo; Song, Zhongxing; Pan, Linmei; Zhang, Yue; Duan, Jinao
Abstract: Membrane technology is a viable alternative to many conventional methods currently used to process traditional Chinese medicine (TCM). However, membrane fouling is a significant obstacle to the application of membrane technology in TCM. In this study, the ultrafiltration (UF) membrane fouling from TCM water extracts under constant transmembrane pressure (TMP) and constant flux operation was studied in connection with critical and threshold flux determinations. Meanwhile, the physicochemical foulant–membrane interactions were analyzed using the extended Derjaguin, Landau, Verwey, and Overbeek (XDLVO) theory. At constant TMP operation, the high pressure resulted in a rapid drop in permeate flux at the start of the filtration period, but the steady-state fluxes did not increase significantly with an increase in TMP. At constant flux operation, the TMP increased somewhat when the permeate flux was below the threshold flux. Fouling was severe above the threshold flux, and the TMP rapidly increased. By displaying fouling resistance as a function of permeate volume, the constant flux operation was compared to a constant TMP operation beginning at the same flux imposed during the constant flux operation. Below the threshold flux, fouling resistance was similar for constant TMP and constant flux operations. However, above the threshold flux, fouling resistance under constant flux operation was much greater than fouling resistance under constant TMP operation. The results of physicochemical interactions showed that there are attractive interactions between hydrophobic membrane and foulants in the TCM water extracts. These interactions should be considered a key factor leading to serious membrane fouling. Highlights: Effect of operation mode on membrane fouling from Chinese medicine water extracts is first studied. Below the threshold flux, fouling is similar for constant pressure and constant flux operations. Above the threshold flux, fouling under constant flux is greater than that under constant pressure. There are attractive interactions between hydrophobic membrane and foulants in the Chinese medicine water extracts.